ANALISIS YURIDIS OPERASI TANGKAP TANGAN (OTT) DALAM PERKARA TINDAK PIDANA KORUPSI SEBAGAI UPAYA PEMBERANTASAN DAN PENCEGAHAN KORUPSI (STUDI PADA POLRESTABES MEDAN) - Ucox Pratua Nugraha; Madiasa Ablisar; Sunarmi Sunarmi; Mahmud Mulyadi (USU LAW JOURNAL, 2018)
ABSTRACT   Corruption takes place at every level and aspect of community life, ranging from Administering Building Permits (IMB), procurement projects in government agencies to law enforcement itself. There are some who argue that corruption has become a culture for the people of Indonesia. Without realizing it, corruption arises from a habit that is considered normal and commonplace by the general public, such as giving gifts to officials / civil servants or their families as a service reward. The habit is commonly seen as part of an eastern culture. This habit gradually became the real seed of corruption. The practice of corruption has been so great in coloring the everyday life of the Indonesian nation. Regarding M. Hatta's opinion, corruption in such a situation is already regarded as a nation's culture. In this research try to analyze the Operation Hand Capture (OTT) conducted by Tim Saber Pungli Subnit Tipikor Polrestabes Medan whether can be made as effort eradication and prevention of corruption, or not. The short chronology of OTT Tim Saber Pungli Subnit Correctional Polrestabes Medan in the Implementation Unit Weighing Motor Vehicles (UPPKB) / Timbang Bridge Sibolangit, Deli Serdang District, Jamin Ginting Road Bandar Baru Village, Sibolangit Subdistrict, Deli Serdang Regency, North Sumatra Province.   Keywords : Operation Hand Capture; Corruption; and Polrestabes Medan.